Enhancing physiology learning through group dynamics: outcomes and perceptions of medical students - Tutor, Antonio S.; Del Nogal Avila, Maria; Muñoz, Úrsula; Sánchez-Vera, Isabel (Frontiers in Physiology, 2025)
BackgroundIn health sciences education, active learning strategies are increasingly recognized for their role in enhancing student engagement and competency development. This study explores the impact of a structured group dynamics activity, framed within a desert survival scenario, on decision-making, teamwork, and academic performance among second-year medical students studying renal physiology.MethodsA mixed-methods design was used involving 195 students, 140 of whom participated in a two-session collaborative activity grounded in physiological knowledge. The intervention emphasized individual and collective decision-making, followed by a teamwork-based quiz to reinforce theoretical content. Academic performance was evaluated using scores from a standardized multiple-choice exam. Student perceptions were gathered through Likert-scale and open-ended surveys.ResultsStudents who participated in the group activity showed significantly higher percentages of correct answers in the renal physiology exam section compared to non-participants (p < 0.05), suggesting a positive association with improved performance and fewer incorrect or unanswered items. Differences in other content blocks (digestive and endocrine physiology) were smaller and not statistically significant. Survey responses indicated overwhelmingly positive perceptions of the activity, particularly regarding its role in reinforcing knowledge, promoting collaborative skills, and fostering an engaging learning environment.ConclusionThese results suggest that participation in a group dynamic activity during physiology sessions could be associated with better academic results related to the content of this activity. While this exploratory study cannot establish causal relationships based on its design, the activity appears particularly beneficial when the scenario design aligns with course content. These results support the pedagogical value of active and collaborative learning in medical education, encouraging the implementation of similar interventions. However, future research should focus on conducting randomized controlled trials with long-term follow-up to establish causality and retention effects.